Savages within the empire : representations of American Indians in eighteenth-century Britain - Bickham, Troy O. (Oxford historical monographs., 2005)
Savages within the Empire explores how Britons perceived and represented American Indians during a time when the empire and its constituent peoples began to capture the nation's sustained attention for the first time. Troy Bickham considers an array of contexts, including newspapers, imperial policy, museum exhibits, the Enlightenment, missionary records, and the public outcry over the use of American Indians as allies during the American War of Independence. He thus. reveals the prevailing pragmatism with which Britons of all ranks approached the empire as well as its impact on British culture.